Prognostic significance of atrial cardiopathy in patients with acute ischemic stroke. (March 2023) - Wu, Yueyang; Yang, Xiaomeng; Jing, Jing; Meng, Xia; Li, Zixiao; Pan, Yuesong; Jiang, Yong; Yan, Hongyi; Huang, Xinying; Liu, Liping; Zhao, Xingquan; Wang, Yilong; et al.
Introduction: Whether atrial cardiopathy is associated with stroke prognosis remains unclear. We evaluated the association between atrial cardiopathy markers and outcomes in patients with ischemic stroke using a nationwide prospective registry. Patients and methods: Based on the Third China National Stroke Registry, we evaluated different atrial cardiopathy markers including increased P-wave terminal force in V1 (PTFV1), advanced interatrial block (aIAB), prolonged P-wave duration, prolonged P-wave dispersion, paroxysmal supraventricular tachycardia, premature atrial contractions, prolonged PR interval, and severe left atrial enlargement in ischemic stroke patients. The outcomes were death and ischemic stroke recurrence at 1 year. The association between atrial cardiopathy markers and outcomes was analyzed using Cox regression models. Results: At 1-year follow-up, 486 (3.4%) patients had died and 1317 (9.3%) patients had experienced ischemic stroke recurrence. After adjustment for clinical risk factors including atrial fibrillation, PTFV1 > 5000 μV·ms (adjusted hazard ratio [HR] 1.70, 95% confidence interval [CI]: 1.18–2.45, p  = 0.004) and aIAB (adjusted HR 1.47, 95% CI: 1.14–1.91, p  = 0.003) were significantly associated with mortality. PTFV1 > 5000 μV·ms was significantly associated with ischemic stroke recurrence (adjusted HR 1.54, 95% CI: 1.22–1.96, p  = 0.0004). This association was observed although we excluded patients diagnosed with atrial fibrillation. Discussion and Conclusion: Atrial cardiopathy markers, especially PTFV1 and aIAB, are significantly associated with a higher risk of poor prognosis in patients with ischemic stroke.